Ending hunger challenge badge - Swedish International Development Agency (SIDA); Youth and United Nations Global Alliance (YUNGA); Food and Agriculture Organization of the United Nations; World Food Programme (WFP); World Organization of the Scout Movement (WOSM) ([Rome] : Food and Agriculture Organization of the United Nations, 2013)
The Ending Hunger Challenge Badge is designed to help educate children and young people about the effects of hunger in the world and how we can put an end to it. This material is appropriate for use in school classes, Guide or Scout groups or youth meetings generally. It includes a wide range of activities and ideas to stimulate learning about hunger and nutrition issues, while motivating children and young people to get involved in the fight against world hunger
Keywords: Hunger -- Prevention